Next level? Civil society’s navigation of multi-level governance in the conflict over cycling conditions in Bavaria - Anna Loffing; Meike Levin-Keitel (European Journal of Spatial Development, 2025)
This article argues that a crucial step towards a more nuanced understanding of civil society conflicts surrounding the mobility transition is the adoption of a spatial perspective, which considers the navigation of the involved levels of governance. To this end, we propose an analytical approach based on Conflict Field Analysis, the Embedded Agency Perspective, and multi-level governance theory: a multi-level analysis of spatially embedded conflicts. The aim of this article is to conduct a qualitative case study on how civil society actors engage with the multi-level governance system in the conflict over cycling conditions in Bavaria between 2017 and 2023. We identify three modes of engagement: firstly, addressing the established governance levels according to their respective competencies; secondly, challenging the allocation of decision-making powers across governance levels; and thirdly, co-creating new governance levels.